Where are we going for the treatment in ischaemic stroke: a comprehensive study of investigator-sponsored randomised controlled trials, 1990–2024 - Anxin Wang; Xue Tian; Meng Gao; Xinya Li; Xue Xia; Ruobing Tian; Manqi Zheng (Stroke and Vascular Neurology)
Background Until recently, a comprehensive understanding of the current development status and emerging trends of investigator-sponsored randomised controlled trials (RCTs) for the treatment of ischaemic stroke (IS) on a global scale remains elusive, making it unclear where the research and innovation in the field are going.Methods Following the design, registration, enrolment and publication (DREP) cycle, we conducted an observational study of investigator-sponsored RCTs enrolling patients with IS for therapeutic purposes using the International Clinical Trial Registry Platform. We analysed cumulative publication rates since registration and enrolment and explored the association of potential factors with publication status.Results A total of 1518 trials were included. The number of registered, enrolment-commenced, published RCTs increased from 1990 to 2024 (p<0.001, for all). Of these, 66.5% were registered prior to their enrolment with the first subject. Among 435 trials that ended and were registered 5 years ago, 189 (43.4%) have been published. Multivariable Cox regression analysis revealed that endovascular therapy or surgery as intervention (compared with traditional medicine) (HR (95% CI), 2.02 (1.06 to 3.87)) was associated with trial publication. Also, there existed a positive association between target sample size and publication, when the sample size surpassed 274. In addition, the most frequent cause of the termination and withdrawal in trials is the difficulty in enrolment.Conclusion Since 1990 to the present, investigator-sponsored RCTs of IS treatment have seen a significant increase worldwide. Nevertheless, a multitude of impediments in the DREP cycle still persists that necessitate resolution and enhancement. There is a pressing need for addressing issues such as retrospective registration, premature termination of enrolment and suppression of study results, to further expand the reach of research improvements to a wider patient community.